2017
DOI: 10.1002/jclp.22562
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of the relationship between rational beliefs and psychological distress

Abstract: The results add empirical evidence for the underling theory of REBT and revealed that the strength of the association between rational beliefs and distress is robust for a wide range of emotional problems. Therefore, rational beliefs could be a trans-diagnostic protective factor against distress. Moreover, results emphasized that rational beliefs type is an important factor, suggesting an increased focus in therapy on the developing of unconditional acceptance and self-acceptance beliefs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 27 publications
(44 reference statements)
2
16
0
Order By: Relevance
“…This group of irrational beliefs reveals absolutist ways of thinking and cause emotional distress. This data is in line with meta-analysis study of Oltean and David ( 2018 ) that identified an average negative correlation between rational beliefs (related to preferences, non-catastrophizing of events, high tolerance for frustration, and acceptance of oneself, others/life) and psychological distress. Unconditional acceptance of self, others, and/or life play a central role as a protective factor against mental disorders, regardless of age or gender.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This group of irrational beliefs reveals absolutist ways of thinking and cause emotional distress. This data is in line with meta-analysis study of Oltean and David ( 2018 ) that identified an average negative correlation between rational beliefs (related to preferences, non-catastrophizing of events, high tolerance for frustration, and acceptance of oneself, others/life) and psychological distress. Unconditional acceptance of self, others, and/or life play a central role as a protective factor against mental disorders, regardless of age or gender.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, those who received Psychoeducation became more apt to recognize and question traditional beliefs that used to conflict with the exercise of their legitimate rights. A more flexible thinking can contribute to reduce suffering (Crum, 2019 ; Oltean & David, 2018 ). The knowledge of their own beliefs and feelings (REBT group) and interpersonal rights (Psychoeducational group) contributed to the improvement of assertive behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the results of the present study may be seen as offering a way to bridge the gap between the fields of clinical and positive psychology. Given the fact that rational beliefs are negatively associated with negative mental health states (David, ; Hyland, Maguire, et al, ; Oltean & David, in press) and, at same time, are positively associated with positive mental health states such as happiness and optimism, clinical work could potentially be simplified by focusing attention on rational beliefs, and thereby modulating positive and negative emotions simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…and populations (David et al, 2005). Results of recent meta-analysis related to the relationship between both irrational and rational beliefs and psychological distress show a positive correlation between irrational beliefs and various types of psychological distress such as anxiety, depression, general distress, anger, and guilt (Vîsla et al, 2016), and a negative association between rational beliefs and psychological distress, with the strongest association being for unconditional acceptance beliefs (Oltean and David, 2018). A thorough review and meta-analysis of REBT over the last 50 years demonstrates the efficacy and effectiveness of REBT interventions in the format of psychotherapy, psychoeducation, or counseling for various conditions regardless of age, clinical status, and delivery format (David et al, 2018).…”
Section: Overview Of Rebtmentioning
confidence: 99%